Morphological and molecular characterization of Aphelenchoides fujianensis n. sp. (Nematoda: Aphelenchoididae) from Pinus massoniana in China - Zhuo, Kan; Cui, Ruqiang; Ye, Weimin; Luo, Mei; Wang, Honghong; Hu, Xuenan; Liao, Jinling (Zootaxa, 2010)
Aphelenchoides fujianensis n. sp. is described and illustrated from a dead Pinus massoniana based on morphology and molecular analyses of the near-full-length small subunit rDNA gene and partial cytochrome oxidase subunit I of mitochondrial DNA. This new species belongs to the Group 3 of Aphelenchoides species sensu Shahina with star-shaped tail terminus and is characterised by a relatively long body (653–843 μ m in the male and 803–941 μ m in the female) and four lateral incisures in the lateral field. The male has relatively large spicules (24–30 μ m). The female has elongate postvulval uterine sac (extending ca 32–44% of vulva-anus distance), usually with sperms. Both male and female have star-shaped mucro. It is distinguished from other species by postvulval uterine sac length, a and c ratios, and spicule size and shape. Molecular analysis reveals that this species has unique 18S and mt-DNA sequences, and is closest to Aphelenchoides besseyi in dendrograms inferred using both markers. The identification codes of OEPP/EPPO for A. fujianensis n. sp. are: A1-B2-C1-D1/3-E1-F1/2.